Antibiotics Effects on biomass, area coverage and chlorophyll of Lemna gibba and Azolla filiculoides - Maldonado Jimenez, Ingrid (2023)
The concentrations of antibiotic residues in aquatic ecosystems are experiencing a progressive increase, which is exerting significant impacts on resident species. The species Lemna gibba and Azolla filiculoides are widely known in studies of toxicity and phytoremediation. Furthermore, these species have been observed to exhibit interesting responses to exposure to antibiotic compounds. In this study, the effects of azithromycin, ciprofloxacin, amoxicillin, cephalexin, ampicillin, and clindamycin (0.00, 2.5, 5, 7.5 mg/L) on biomass, Relative Growth Rate (RGR), percentage of area, and chlorophyll were evaluated over a period of 7 days. Biomass data were collected to calculate RGR, and daily images of each experimental unit were captured to estimate the percentage of area coverage and RGB bands for chlorophyll calculation purposes. The results revealed toxic effects of the concentrations compared to the control group, with Azolla showing greater susceptibility than Lemna. Concerning the percentage of area coverage, the experimental days significantly influenced Azolla (p-value = <2e-16), while both the antibiotic concentration and the duration of exposure negatively affected Lemna, with p-values of 0.00161 and 2.1e-11, respectively. As for chlorophyll levels, no significant alterations were detected in response to the evaluated concentrations. These findings demonstrate that despite the adverse effects of antibiotics, the investigated species still exhibit survival and antibiotic removal capabilities.